2004
DOI: 10.1029/2003jb002582
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic controls on the frictional behavior of dry and water‐saturated sheet structure minerals

Abstract: [1] We compare the frictional strengths of 17 sheet structure mineral powders, measured under dry and water-saturated conditions, to identify the factors that cause many of them to be relatively weak. The dry coefficient of friction m ranges upward from 0.2 for graphite, leveling off at 0.8 for margarite, clintonite, gibbsite, kaolinite, and lizardite. The values of m (dry) correlate directly with calculated (001) interlayer bond strengths of the minerals. This correlation occurs because shear becomes localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
236
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(271 citation statements)
references
References 54 publications
30
236
5
Order By: Relevance
“…Clay-poor gouge samples likely experienced substantial grain-size reduction and compaction, resulting in slip hardening (e.g., Morrow and Byerlee 1989). In contrast, in clay-rich gouge samples, initial compaction hardening was likely followed by weakening due to preferred alignment of clay minerals along shear planes (e.g., Moore and Lockner 2004). Except for siltstone sample C2652 and tuff sample C9087, whose (a − b) and Δμ ss /ΔlnV sliding values are smaller than those of the other samples, there is a tendency for the (a − b) value to decrease while the Δμ ss / ΔlnV sliding value increases with increasing clay mineral content (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Clay-poor gouge samples likely experienced substantial grain-size reduction and compaction, resulting in slip hardening (e.g., Morrow and Byerlee 1989). In contrast, in clay-rich gouge samples, initial compaction hardening was likely followed by weakening due to preferred alignment of clay minerals along shear planes (e.g., Moore and Lockner 2004). Except for siltstone sample C2652 and tuff sample C9087, whose (a − b) and Δμ ss /ΔlnV sliding values are smaller than those of the other samples, there is a tendency for the (a − b) value to decrease while the Δμ ss / ΔlnV sliding value increases with increasing clay mineral content (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Moore and Lockner (2004) suggested that the (001) bonding strength is a primary factor controlling frictional coefficient of the sheet silicates; however, recent experiments by Behnsen and Faulkner (2012) found the friction coefficient of various clay minerals were deviated significantly from the value predicted from the electrostatic separation energy. Sakuma and Suehara (2015) calculated interlayer bonding energy using the first-principles based density functional theory without using the empirical approximation of charge distributions in minerals, and they showed that there is no clear correlation with the frictional strength for layered minerals.…”
Section: Effect Of Humidity and Interlayer Cations On The Frictional mentioning
confidence: 99%
“…Several previous reports indicated that X-ray diffraction (XRD) is still the most widely used method for characterizing the structure of OMt in water, and the results showed that water molecules can always cause evident swelling of OMt [33][34][35][36]. According to the XRD characterization results, Zhu et al [18] recently proposed a set of structural models for wet OMt.…”
Section: Introductionmentioning
confidence: 99%